Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Auditor Kantor Badan Pemeriksa Keuangan Wilayah Lampung (Study Kasus di Kantor BPK Wilayah Lampung) - Rosmiaty Tarmizi; Gilang Suryo Dewantoro; Suwandi SUWANDI (Jurnal Akuntansi dan Keuangan, 2012)
The purpose of this research is to analyze influence emotional intelligence and wit spiritual on the performance bpk auditor office region lampung. While hypothesis advanced by is there are good influence simultaneously or by partial between intelligence emotional and intelligence spiritual on the performance auditor. The research found that simultaneously emotional intelligence and wit spiritual effect on performance auditor. Results in partial show that emotional intelligence and wit spiritual effect on performance auditor. Then can be concluded that emotional intelligence and wit spiritual effect on auditor good performance simultaneously or by partial.